2023
DOI: 10.1007/s13668-023-00448-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotic and Selenium Co-supplementation on Lipid Profile and Glycemia Indices: A Systematic Review and Meta-analysis of Randomized Clinical Trials

Abstract: Purpose of Review The current systematic review and meta-analysis was done to evaluate the effects of selenium and probiotic co-supplementation on lipid profile and glycemia indices of the adult population using randomized controlled clinical trials (RCTs). Recent Findings Five studies involving 282 participants with a sample size ranging from 38 to 79 were eligible to be enrolled in the current study. Co-supplementation with probiotic and selenium reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Also, a meta-analysis of five studies published up to February 2022 where joint probiotic and Se (at 50-200 µg/day) supplementations in groups of adults representing various populations were applied showed that the treatment resulted in a significant WMD of FG (−4.0 mg/dL), FI (−2.5 µIU/mL), HOMA-IR (−0.6), TG (−14.4 mg/dL), TC (−12.8 mg/dL), and LDL (−7.1 mg/dL) [187]. All of these values except for FI and HOMA-IR were much greater than those found by meta-analyses studying the effects of Se alone (see Tables 5 and 6), suggesting that joint Se and probiotic treatment may indeed be more effective in improving the homeostasis of glucose and lipids.…”
Section: Supplementation In Treatmentmentioning
confidence: 99%
“…Also, a meta-analysis of five studies published up to February 2022 where joint probiotic and Se (at 50-200 µg/day) supplementations in groups of adults representing various populations were applied showed that the treatment resulted in a significant WMD of FG (−4.0 mg/dL), FI (−2.5 µIU/mL), HOMA-IR (−0.6), TG (−14.4 mg/dL), TC (−12.8 mg/dL), and LDL (−7.1 mg/dL) [187]. All of these values except for FI and HOMA-IR were much greater than those found by meta-analyses studying the effects of Se alone (see Tables 5 and 6), suggesting that joint Se and probiotic treatment may indeed be more effective in improving the homeostasis of glucose and lipids.…”
Section: Supplementation In Treatmentmentioning
confidence: 99%